FORMATION OF A SCIENTIFIC AND GENERAL-CULTURAL OUTLOOK IN THE EDUCATIONAL PROCESS - Boliqulova Madinabonu; Shamuradova Naima (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The formation of scientific and cultural worldviews in the educational process has a significant impact on students’ personality, culture, and intellectual development. Scientific worldview primarily encompasses logical thinking, problem analysis, and the use of scientific methodologies. On the other hand, cultural worldview ensures an understanding of social, cultural, and ethical values. The interconnection of these processes serves to enhance the quality of education, support students’ personal development, and bring about positive changes in society.